Financial Sector Assessment : Russian Federation - World Bank; International Monetary Fund (World Bank, Washington, DC, 2016)
A joint IMF-World Bank mission visited the Russian Federation from March 15 to 31, 2016, to conduct an assessment under the Financial Sector Assessment Program (FSAP). The mission assessed financial sector risks and vulnerabilities, assessed the quality of financial sector supervision, and evaluated financial safety net arrangements. The mission also assessed financial inclusion for individuals, the role of the state in the financial sector, insurance sector development, and the payment system.